The millennial maze : sorting out evangelical options - Grenz, Stanley J. (Stanley James), 1950-2005 (Downers Grove, Illinois IVP, 1992)
"In this book Stanley J. Grentz provides historical and biblical, as well as theological, perspective on the four major poistions held by evangelicals--postmillennialism, dispensational premillennialism, historic premillennialism and amillennialism. Assessing the strengths and weaknesses of each position, he seeks to cut a new path through the maze that reaffirms the valid insights of each and sounds a fresh note of hope in an age of shattered illusions. As an added bonus readers will find that Grenz takes note of some of the latest developments in the dialog between dispensationalists and covenant theologians. The result has been some modifications in long-held positions that have brought the two groups closer together" -- page 4 of cover.
Preface -- Introduction -- 1. The nearness of the end : the millennium question in the Bible & in the present -- 2. Anticipating the end : millenarianism in the history of the church -- 3. Bringing in the kingdom :the heritage of postmillennialism -- 4. A future kingdom for Israel :the ascendancy of dispensationalism -- 5. Millennial blessings for the church: historic premillennialism -- 6. A golden age beyond time : amillennialism -- 7. Optimism-pessimism-realism: the theological significance of the millennium issue -- 8. Our present in the light of God's future: the significance of corporate eschatology -- Notes.
Includes bibliographical references (unnumbered page 217-page 239).
Keywords: Millennialism; Dispensationalism; Eschatology; Evangelicalism